Uji Kinerja Alat Pencacah Rumput (Mini Chopper) Type TMB 01 - S, Rizki Kurniawan; Tamrin, Tamrin; Asmara, Sandi; Kuncoro, Sapto (abe.fp.unila.ac.id, 2024)
The high amount of food crop production in East Lampung Regency produces abundant biomass. This biomass can be used as silage for animal feed. A grass chopper is needed to make silage. The aim of the research was to test the performance of the TMB 01 type grass chopper on corn stalks and elephant grass with engine rotation speeds of 800, 1000 and 1200 rpm. This research was carried out in June - November 2023, at the Self-Help Agricultural and Rural Training Center (P4S) Tani's Market Balerejo, East Lampung Regency. This research was carried out with observation parameters measuring chopping time, measuring machine rotation speed, measuring fuel consumption, measuring the diversity of biomass mass that had been chopped. The research results show that rotational speed (rpm) influences work capacity, working time, fuel consumption and chopping diversity. The best rotation speed of the shredding machine is 1200 rpm. Keywords: Biomass, Engine Revolution, Shredding Machine, Work Capacity.